Rubber toughened polypropylene nanocomposite : effect of compatibilizer content on phase morphology and mechanical properties - Lim, Jian Wei; Azman Hassan; Mat Uzir Wahit; Abdul Razak Rahmat; International Conference and Exhibition on Macromolecular Science and Its Impact on Industries (2004 : Kuala Lumpur) (Skudai : Universiti teknologi Malaysia, 2004)
54